Factors associated with uptake of services to prevent mother-to-child transmission of HIV in a community cohort in rural Tanzania. (4th June 2015) - Gourlay, Annabelle; Wringe, Alison; Todd, Jim; Cawley, Caoimhe; Michael, Denna; Machemba, Richard; Reniers, Georges; Urassa, Mark; Zaba, Basia
Abstract : Objectives: This study aimed to identify factors associated with access to HIV care and antiretroviral (ARV) drugs for prevention of mother-to-child transmission (PMTCT) of HIV among HIV-positive pregnant women in a community cohort in rural Tanzania (Kisesa). Methods: Kisesa-resident women who tested HIV-positive during HIV serosurveillance and were pregnant (while HIV-positive) between 2005 and 2012 were eligible. Community cohort records were linked to PMTCT and HIV clinic data from four facilities (PMTCT programme implemented in 2009; referrals to city-based hospitals since 2005) to ascertain service use. Factors associated with access to HIV care and ARVs during pregnancy were analysed using logistic regression. Results: Overall, 24% of women accessed HIV care and 12% accessed ARVs during pregnancy (n=756 pregnancies to 420 women); these proportions increased over time. In multivariate analyses for 2005–2012, being married, prior voluntary counselling and testing, increasing age, increasing year of pregnancy and increasing duration of infection were independently associated with access to care and ARVs. Residence in roadside areas was an independent predictor of access to care but not ARVs. There was no evidence of an interaction with time period. Conclusions: Access to PMTCT services was low in this rural setting but improved markedly over time. There were fairly few sociodemographic differentials although support for young women and those without partners may be needed. Further decentralisation of HIV services to more remote areas, promotion of voluntary counselling and testing and implementation of Option B+ are likely to improve uptake and may bring women into care and treatment sooner after infection.